2015
DOI: 10.1007/s12040-014-0533-x
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of vertical mass changes in the south of Izmir (Turkey) by monitoring microgravity and GPS/GNSS methods

Abstract: The monitoring of gravity changes in a region enables the investigation of regional structural elements depending upon the changes in load compensation. This method, preferred in recent years, has yielded good results from different parts of the world for determination of the deformation at fields. With the addition of GPS/GNSS monitoring to microgravity studies, the mass changes within the crust in vertical directional movements of a region can be estimated. During GPS/GNSS monitoring and microgravity studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Regional studies have suggested that a N-S extension is dominant in the region and the mean motion of the region was approximately 25 mm/year towards the SW in Eurasia fixed frame solutions. Only 4 of these studies, in which the newest measurement was made in 2012, have focused on İzmir and its immediate surroundings, where the study area is located (Aktuğ and Kılıçoğlu, 2006;Özener et al, 2012;Pamukçu et al, 2015;Çırmık et al, 2017a). However, the results herein indicated that a strike-slip tectonic regime was the main reason for the present-day deformation in the southern part of the İBTZ.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Regional studies have suggested that a N-S extension is dominant in the region and the mean motion of the region was approximately 25 mm/year towards the SW in Eurasia fixed frame solutions. Only 4 of these studies, in which the newest measurement was made in 2012, have focused on İzmir and its immediate surroundings, where the study area is located (Aktuğ and Kılıçoğlu, 2006;Özener et al, 2012;Pamukçu et al, 2015;Çırmık et al, 2017a). However, the results herein indicated that a strike-slip tectonic regime was the main reason for the present-day deformation in the southern part of the İBTZ.…”
Section: Discussionmentioning
confidence: 75%
“…Several studies with new GPS/GNSS measurements have been conducted in western Anatolia over the last 2 decades (McClusky et al, 2000;Aktuğ and Kılıçoğlu, 2006;Reilinger et al, 2006Reilinger et al, , 2010Aktuğ et al, 2009;Özener et al, 2012;Pamukçu et al, 2015;Çırmık et al, 2017a). Regional studies have suggested that a N-S extension is dominant in the region and the mean motion of the region was approximately 25 mm/year towards the SW in Eurasia fixed frame solutions.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the years if the gravity changes represent amplitude changes as decreasing, increasing and then decreasing (-+-) or increasing, decreasing and then increasing (-+-), it can be said that this point needs to include the physical parameters which support the elastic behaviour. But, the gravity changes of DEU5 obtained from the microgravity studies realized between 2009-2010-2011 represented increasing character [10]. As the third step, the non-linear soil dynamic analysis were done by using 2D finite element modelling (FEM) program, Phase2 software [11] with the help of the V s values obtained from MASW measurements and calculated elasticity module (E), shear module (G), cohesion (C), angle of internal friction (φ), weight per unit volume (γ) parameters (Table 1).…”
Section: Applicationsmentioning
confidence: 89%
“…The graphical changes over the years in the gravity measurements, which are obtained in a GNSS point, provide importance [10]. Due to the years if the gravity changes represent amplitude changes as decreasing, increasing and then decreasing (-+-) or increasing, decreasing and then increasing (-+-), it can be said that this point needs to include the physical parameters which support the elastic behaviour.…”
Section: Applicationsmentioning
confidence: 99%
“…According to the GNSS and microgravity studies of Pamukçu et al (2015) carried out in the region between the years 2009-2011 where was near to the epicentre of the 30th October 2020 Samos earthquake (Mw = 6.9), the Bozkurt (2001Bozkurt ( , 2007, Gessner et al (2013), Çırmık et al (2016), Çırmık and Pamukçu (2017)).…”
Section: Introductionmentioning
confidence: 99%